2022
DOI: 10.3390/ijtm2010006
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Bacteriuria or Urinary Tract Infection? New and Old Biomarkers

Abstract: Urinary tract infections (UTIs) are among the most common infective disease in the adult population. UTI diagnosis is based essentially on the presence of lower urinary tract symptoms (e.g., dysuria, urgency, and frequency) and the evidence of bacteriuria (by dipstick testing and/or urine culture). UTI diagnosis is not always easy because symptoms can be vague, or patient basal conditions can interfere negatively with the diagnostic process, whereas urine culture is still ongoing. In those cases, the different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The biomarkers used in this study [neutrophil gelatinase-associated lipocalin (NGAL), interleukin-8 (IL-8), and interleukin-1-beta (IL-1β)] are essential components of the constitutive immune response in the urinary tract and have been studied in association with UTIs. Importantly, these three biomarkers have also demonstrated utility for the diagnosis of UTIs [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. One of our previous studies discovered that NGAL, IL-8, and IL-1β have sensitivities of 82.6%, 91.2%, and 69.8% with specificities of 90.8%, 76.8%, and 96.9%, respectively [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The biomarkers used in this study [neutrophil gelatinase-associated lipocalin (NGAL), interleukin-8 (IL-8), and interleukin-1-beta (IL-1β)] are essential components of the constitutive immune response in the urinary tract and have been studied in association with UTIs. Importantly, these three biomarkers have also demonstrated utility for the diagnosis of UTIs [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. One of our previous studies discovered that NGAL, IL-8, and IL-1β have sensitivities of 82.6%, 91.2%, and 69.8% with specificities of 90.8%, 76.8%, and 96.9%, respectively [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their study included a review of 4 previously published studies and suggested that uNGAL offered a promising and more sensitive alternative to the LE test for diagnosing UTI. Martino et al ( 12 ) conducted a systematic review of 4 published studies in an adult population and provided a summary of the results indicating encouraging performance of uNGAL. Horvath et al ( 10 ) summarized 16 studies on uNGAL for predicting UTI in both pediatric and adult population.…”
Section: Discussionmentioning
confidence: 99%
“…The most promising biomarkers identified were neutrophil gelatinase-associated lipocalin (NGAL), matrix metalloproteinase 9 (MMP9), CXCL8 and interleukin-1β (IL-1β). While other targeted approaches over the years have additionally identified interleukin-8, tumor necrosis factor-α, and urine antimicrobial peptides ( 5 7 ) as putative predictors of UTI, the most promising and widely studied UTI biomarker is NGAL ( 8 12 ). Pre-clinical studies have established the biological, teleological, and functional roles of NGAL ( 13 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…The integration of these guidelines ensures a comprehensive and tailored approach to UTI management in kidney transplant recipients. Research into novel antimicrobial agents and immunomodulatory therapies, as well as the significance of innovative nonantibiotic-based approaches, may offer more targeted and effective options, mitigating the risk of infections while minimizing adverse effects [44][45][46][47][48].…”
Section: Management Of Urinary Tract Infections In Elderly Kidney Tra...mentioning
confidence: 99%